THE IMPORTANCE OF SUPEROXIDE DISMUTASE IN THE FORMATION OF ACNE - Nilufar N. Malikova ,; Saidkasim S. Arifov , (Central Asian Journal of Medicine, 2025)
The article provides information on oxidative stress and antioxidant protection, in particular the role of superoxide dismutase in the pathogenesis of acne. The authors' own data on the study of the content of superoxide dismutase (SOD) in the blood serum of acne patients are presented and its statistically significant decrease against the control group is revealed. The low level of SOD depended on the duration and severity of the disease.